2022
DOI: 10.2196/26634
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Prediction Models for Gestational Diabetes Mellitus: Meta-analysis

Abstract: Background Gestational diabetes mellitus (GDM) is a common endocrine metabolic disease, involving a carbohydrate intolerance of variable severity during pregnancy. The incidence of GDM-related complications and adverse pregnancy outcomes has declined, in part, due to early screening. Machine learning (ML) models are increasingly used to identify risk factors and enable the early prediction of GDM. Objective The aim of this study was to perform a meta-an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 59 publications
0
18
0
1
Order By: Relevance
“…Work in pregnancy has employed ML techniques for decades; for example, a recent article reviewed 26 studies that used ML to study the optimal mode of childbirth [ 18 ]. Other work has examined risk factors in pregnancy, including for sepsis [ 19 ], ectopic pregnancy [ 20 ], and gestational diabetes (see [ 21 ] for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Work in pregnancy has employed ML techniques for decades; for example, a recent article reviewed 26 studies that used ML to study the optimal mode of childbirth [ 18 ]. Other work has examined risk factors in pregnancy, including for sepsis [ 19 ], ectopic pregnancy [ 20 ], and gestational diabetes (see [ 21 ] for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [2] measured the risk of bias in the machine learning models with the new prediction model risk of bias assessment tool. e meta-analysis and findings of heterogeneity were done with the help of the Meta Disc software.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within ve to ten years following childbirth, around 50% of women with a history of GDM develop type 2 diabetes. [2]. GDM is a prevalent metabolic illness that is typically a temporary pregnancy disorder.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that current machine learning algorithms are powerful enough to help clinicians determine whether an individual will develop type 2 diabetes in the future. Other researchers [ 16 ] conducted a meta-analysis of machine-learning models for predicting diabetes in pregnant women. It was found that machine learning models were more attractive in predicting diabetes than current traditional screening strategies.…”
Section: Introductionmentioning
confidence: 99%